Acid‐inhibitory effects of vonoprazan 20 mg compared with esomeprazole 20 mg or rabeprazole 10 mg in healthy adult male subjects ‐ a randomised open‐label cross‐over study - Sakurai, Y.; Mori, Y.; Okamoto, H.; Nishimura, A.; Komura, E.; Araki, T.; Shiramoto, M. (Alimentary pharmacology & therapeutics, 2015)
Summary Background Proton pump inhibitors (PPIs) are widely used for the treatment of acid‐related diseases. Vonoprazan is a member of a new class of acid suppressants; potassium‐competitive acid blockers. Vonoprazan may thus be an alternative to PPIs. Aim To evaluate efficacy, rapidity and duration of acid‐inhibitory effects of vonoprazan vs. two control PPIs, esomeprazole and rabeprazole, in 20 healthy Japanese adult male volunteers with CYP2C19 extensive metaboliser genotype. Methods In this randomised, open‐label, two‐period cross‐over study, vonoprazan 20 mg and esomeprazole 20 mg (Study V vs. E) or rabeprazole 10 mg (Study V vs. R) were orally administered daily for 7 days. Primary pharmacodynamic endpoint was gastric pH over 24 h measured as percentage of time pH ≥3, ≥4 and ≥5 (pH holding time ratios; HTRs) and mean gastric pH. Results Acid‐inhibitory effect (pH4 HTR) of vonoprazan was significantly greater than that of esomeprazole or rabeprazole on both Days 1 and 7; Day 7 difference in pH4 HTR for vonoprazan vs. esomeprazole was 24.6% [95% confidence interval (CI): 16.2–33.1] and for vonoprazan vs. rabeprazole 28.8% [95% CI: 17.2–40.4]. The Day 1 to Day 7 ratio of 24‐h pH4 HTRs was >0.8 for vonoprazan, compared with 0.370 for esomeprazole and 0.393 for rabeprazole. Vonoprazan was generally well tolerated. One vonoprazan subject withdrew due to a rash which resolved after discontinuation. Conclusions This study demonstrated a more rapid and sustained acid‐inhibitory effect of vonoprazan 20 mg vs. esomeprazole 20 mg or rabeprazole 10 mg. Therefore, vonoprazan may be a potentially new treatment for acid‐related diseases.